Assignment of the disulfide bridges in bothropstoxin-I, a myonecrotic Lys49 PLA(2) homolog from Bothrops jararacussu snake venom - Cintra, ACO; Sampaio, S. V.; Raghuvir, A. K.; Giglio, JR (Kluwer Academic/plenum Publ, 2001)
Bothropstoxin-I (BthTX-1), a Lys49 phospholipase A(2) homolog with no apparent catalytic activity, was first isolated from Bothrops jararacussu snake venom and completely sequenced in this laboratory. It is a 121-amino-acid single polypeptide chain, highly myonecrotic, despite its inability to catalyze hydrolysis of egg yolk phospholipids, and has 14 half-cystine residues identified at positions 27, 29, 44, 45, 50, 51, 61, 84, 91, 96, 98, 105, 123, and 131 (numbering according to the conventional alignment including gaps, so that the last residue is Cys 131). In order to access its seven disulfide bridges, two strategies were followed: (1) Sequencing of isolated peptides from (tryptic + SV8) and chymotryptic digests by Edman-dansyl degradation; (2) crystallization of the protein and determination of the crystal structure so that at least two additional disulfide bridges could be identified in the final electron density map. Identification of the disulfide-containing peptides from the enzymatic digests was achieved following the disappearance of the original peptides from the HPLC profile after reduction and carboxymethylation of the digest. Following this procedure, four bridges were initially identified from the tryptic and SV8 digests: Cys50-Cys131, Cys51-Cys98, Cys61-Cys91, and Cys84-Cys96. From the chymotryptic digest other peptides were isolated either containing some of the above bridges, therefore confirming the results from the tryptic digest, or presenting a new bond between Cys27 and Cys123. The two remaining bridges were identified as Cys29-Cys45 and Cys44-Cys105 by determination of the crystal structure, showing that BthTX-1 disulfide bonds follow the normal pattern of group II PLA(2)s.
Keywords: bothropstoxin-I; myonecrosis; phospholipase A(2); disulfide bridges